Single Nucleotide Polymorphisms in Regulator-Encoding Genes Have an Additive Effect on Virulence Gene Expression in a Vibrio cholerae Clinical Isolate - Bailey M. Carignan (American Society for Microbiology, 2016)
ABSTRACT Vibrio cholerae is the etiological agent of the infectious disease cholera, which is characterized by vomiting and severe watery diarrhea. Recently, V. cholerae clinical isolates have demonstrated increased virulence capabilities, causing more severe symptoms with a much higher rate of disease progression than previously observed. We have identified single nucleotide polymorphisms (SNPs) in four virulence-regulatory genes (hapR, hns, luxO, and vieA) of a hypervirulent V. cholerae clinical isolate, MQ1795. Herein, all SNPs and SNP combinations of interest were introduced into the prototypical El Tor reference strain N16961, and the effects on the production of numerous virulence-related factors, including cholera toxin (CT), the toxin-coregulated pilus (TCP), and ToxT, were analyzed. Our data show that triple-SNP (hapR hns luxO and hns luxO vieA) and quadruple-SNP combinations produced the greatest increases in CT, TCP, and ToxT production. The hns and hns luxO SNP combinations were sufficient for increased TCP and ToxT production. Notably, the hns luxO vieA triple-SNP combination strain produced TCP and ToxT levels similar to those of MQ1795. Certain SNP combinations (hapR and hapR vieA) had the opposite effect on CT, TCP, and ToxT expression. Interestingly, the hns vieA double-SNP combination strain increased TCP production while decreasing CT production. Our findings suggest that SNPs identified in the four regulatory genes, in various combinations, are associated with increased virulence capabilities observed in V. cholerae clinical isolates. These studies provide insight into the evolution of highly virulent strains. IMPORTANCE Cholera, an infectious disease of the small intestine caused by the aquatic bacterium Vibrio cholerae, often results in vomiting and acute watery diarrhea. If left untreated or if the response is too slow, the symptoms can quickly lead to extreme dehydration and ultimately death of the patient. Recent anecdotal evidence of cholera patients suffering from increasingly severe symptoms and of disease progression at a much higher rate than previously observed has emerged. As recent cholera outbreaks caused by increasingly virulent strains have resulted in higher mortality rates, the need to investigate the mechanism(s) allowing this observed increased virulence is apparent. The significance of our research is in identifying the mechanism for increased virulence capabilities, which will allow the development of a model that will greatly enhance our understanding of cholera disease and V. cholerae pathogenesis, leading to broader biomedical impacts, as cholera serves as a model for other enteric diarrheal diseases.